SOSIALISASI PEMANFAATAN LIMBAH AMPAS TEBU SEBAGAI BAHAN SUBSTITUSI SEBAGIAN SEMEN PADA PAVING BLOCK DI KELURAHAN PADANG MATINGGI LESTARI KOTA PADANGSIDEMPUAN: Socialization Of The Utilization Of Sugarbean Waste As A Partial Substitutional Material For Cement In Paving Block In Padang Matinggi Lestari Village, Padangsidempuan City - Rizky Febriani Pohan; Muhammad Rahman Rambe; Nurhasana Siregar; Sahrul Harahap (Forind Press, 2023)
Utilization of sugarbean waste as a partial substitutional material for cement in paving block is ​​an effort to decrease of cement use in construction materials for increasing paving block quality. This article was written as a result of socialization to provide Padang Matinggi Lestari Village, Padangsidempuan City construction workers’s knowledge and their skills about the utilize of sugarbean waste as a partial substitutional material so that paving block was be better and had high quality . Methods of delivery of activities consisted of lectures/presentations, discussions and questions and answers. After the socialization finish, the results of the activity were monitored for 1 month to know that activity’s output happened or not. The results of this activity show that more than 60% of the participants do not know/heard about the utilize of sugarbean waste as a partial substitutional material for cement in paving block. However, more than 60% of the participants are interested. The enthusiasm of the participants to take part in this socialization activity is very high, because 90% of the partners find this socialization very useful, including knowing how to collect and sort sugarbean waste around their area. The success of this activity is reflected in the very high enthusiasm and presention of the participants. The results of monitoring for 1 month indicate that a follow-up plan is needed to correct deficiencies in the outreach activities.